2020
DOI: 10.1155/2020/6978171
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Preconception Care and Associated Factors among Healthcare Providers Working in Public Health Institutions in Awi Zone, North West Ethiopia, 2019: Institutional-Based Cross-Sectional Study

Abstract: Background. Preconception care is a set of interventional care for the better maternal and childbirth outcome. Nevertheless, this area still faces implementation problems in most of the developing countries including Ethiopia. Objective. To assess the knowledge of preconception care and associated factors among healthcare providers working in public health institutions in Awi zone, North West Ethiopia. Method. An institutional-based cross-sectional study was conducted among 660 healthcare providers working in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 8 publications
(16 reference statements)
4
23
1
Order By: Relevance
“…Health care providers who earn better monthly salary had good level of knowledge. Which is in line with a study conducted in Hawassa, (13) and Awi (20) in Ethiopia. Knowledge difference among higher and lesser salaries may not afford to have smart phones to access medical information and unable to pay for internet.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Health care providers who earn better monthly salary had good level of knowledge. Which is in line with a study conducted in Hawassa, (13) and Awi (20) in Ethiopia. Knowledge difference among higher and lesser salaries may not afford to have smart phones to access medical information and unable to pay for internet.…”
Section: Discussionsupporting
confidence: 92%
“…The nding of the study revealed that 49.1% (95% CI: 44.8-53.3%) of healthcare providers had good level of knowledge on preconception care which is consistent with the nding reported in Awi zone which showed 52% (20). However, higher than the study done in Hawassa City ( 31%) (13) and lower than in Addis Ababa (69.2%) (16) and South Africa (55%) (11).…”
Section: Discussionsupporting
confidence: 83%
“…For instance, a community-based study in Wolayita [ 27 ] and Gojjam [ 28 ], Ethiopia, showed that 53% and almost 28% of mothers knew preconception healthcare, respectively. Even though it is essential, preconception health is yet not integrated into the present healthcare system in Ethiopia [ 29 , 30 ]. Hence, preconception healthcare may be a missed opportunity that the maternal healthcare system of Ethiopia should account for [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the couple’s intention to seek out PCC is insufficient 23 . Different studies in Ethiopia showed the women’s knowledge of PCC as a basic issue for implementation of a maternal continuum of care 27 29 However, none of them are inconclusive in determining the knowledge level and its predictors.…”
Section: Introductionmentioning
confidence: 99%